(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Cement production gives rise to CO2 emissions generated by calculations of CaCO3 and by fossil, being responsible for about 5% of the CO2 emissions in the world. This can be substantially reduced if cement replacement materials, either partial or complete such as fly ash are used. Presently large amounts of fly ash are generated in thermal industries with an important impact on the environment and humans. In recent years many researchers have established the use of supplementary cementitious materials (SCM) like flyash (FA) not only improves the various properties of concrete both in its fresh and hardened states but also can contribute to economic construction costs. Plastic bags which are commonly used for packing, carrying vegetables, etc create a serious environmental problem. The safe disposal of plastic bags in the environment is the most challenging issue for solid waste management across the globe. These are non biodegradable and toxic. Every year at least 15% of total plastic waste remains untreated. Concrete is one of the best choices for construction in many countries today. Waste plastic is being tried in the field of construction as a spatial replacement in fine aggregate, coarse aggregate, or as an additive the concrete. In the present study fly ash (FA) is taken as the partial replacement in cement and low-density polyethylene (LDPE) is used as an additive in the concrete. FA was partially replaced in cement at percentages of 10, 20, and 30. Along with the variation of FA, LDPE was also added from 0.2% to 1% in the concrete by volume. Ample number of samples in M20 grade was prepared with a w/c ratio of 0.55 It was found from the result that the optimum compressive strength for 7 days and 28 days were 28.44 N/mm2 and 33.77N/mm2 obtained at 20% percent replacement of FA with 0.4% addition of LDPE Similarly the optimum split tensile strength for 28 days was 2.49 N/mm2 obtained at 20% replacement of FA with 0.8% addition of LDPE. Thus 20% FA with up to 0.4% LDPE can be adopted so that the disposal of waste plastic and fly ash can be done well as well and the efficiency of the concrete can be managed effectively.